Generate Poems and Letters Using an Iterative Neural Network: (Poem Generating using LSTM) - Mtasher, Ashwaq Katham; Jawad, Wasnaa Kadhim; Zghair, Noor Abdul Khaleq (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Creating a linguistic text using the famous type of recursive neural network: From the well-known section as a section of the main branches of artificial intelligence, we can see that one of the main tasks that fall under this section is to generate a real chat using deep intelligence models and because of its distinctive ability, a text will be generated very close to the level of texts written by real humans and almost The text generated using the model cannot be distinguished as an industrial text because it is very similar to the text written by humans and we see the great future benefit that this new knowledge will achieve in solving many of the various tasks facing the world today for example, translating from language to language, generating novels and poems on the level of art, writing a summary of a long text using intelligence models, enabling the robot to write and generating sounds later. All these tasks will be solved with the help of models of deep intelligence. A modern method will be presented in generating poetry writing using deep model and identification, an iterative neural network that learns through the sequence and remembers it for a short period of time and then generates a similar sequence of letters that will form sentences bearing a poetic meaning.